2014
DOI: 10.1177/0256090920140405
|View full text |Cite
|
Sign up to set email alerts
|

Market Reaction to Stock Dividends: Evidence from India

Abstract: Theoretically, stock dividends have no impact on financial position of the announcing company as net worth and total assets remain the same, though empirical evidence across the globe shows that markets react to stock dividend announcements. The present study analyses the market reaction pertaining to stock dividend decisions in the Indian context. Market reaction has been captured in terms of impact on returns, liquidity, and risk. The sample includes 51 ‘pure’ stock dividend announcements from January 1, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
4
0
3
Order By: Relevance
“…It can be seen that the abnormal return in the Philippines has a positive average. The existence of a positive average abnormal return on the stock market in the Philippines is in accordance with research conducted by Mehta et al [10] which found a positive market reaction in India. This positive reaction shows that investors believe this dividend announcement is a good signal and will be profitable for them.…”
Section: Philippinesupporting
confidence: 90%
“…It can be seen that the abnormal return in the Philippines has a positive average. The existence of a positive average abnormal return on the stock market in the Philippines is in accordance with research conducted by Mehta et al [10] which found a positive market reaction in India. This positive reaction shows that investors believe this dividend announcement is a good signal and will be profitable for them.…”
Section: Philippinesupporting
confidence: 90%
“…Further, it is observed that the information is absorbed faster in a larger firm. Similarly, Mehta et al, (2014) found that the dividend announcement induces an increase in the wealth of the shareholders. Anwar et al, (2015;2017) examined the impact of the cash dividend on the stock return and provided strong evidence supporting the 'dividend signalling' and 'risk information' hypothesis.…”
Section: Review Of Literaturementioning
confidence: 88%
“…Considering the reaction of the Indian Stock market, there exist minimal studies; among them, studies by Mallikarjunappa & Manjunatha (2009), Kumar & G (2013), Mehta et al, (2014) Anwar et al, (2017) observed the significance and positive impact of the dividend announcements on stock return, whereas Saravanakumar (2011), Anwar et al, (2015) found no significant impact of the announcements. On the other hand, Berezinets et al, (2015) and Kumar (2017) found that increased dividend has a positive impact and decreased dividend hurt stock return.…”
Section: Introductionmentioning
confidence: 99%
“…(Garrett & Priestley, 2000) find significant evidence of dividend smoothing and dividend conveying information regarding unexpected positive changes in current permanent earnings. (Mehta, Jain, & Yadav, 2014) Study on Stock dividend shows that announcements induce an increase in the wealth of the shareholders. In India there is price stability.…”
Section: Clientele Effect Theorymentioning
confidence: 99%